A comparison of diet versus diet + exercise programs for health improvement in middle-aged overweight women. (June 2020) - Joseph, Gili; Arviv-Eliashiv, Rinat; Tesler, Riki
Background: Obesity is an independent risk factor for many diseases. Many studies have investigated the benefits of losing weight as well as the best methods for weight loss. This research evaluated the impact of various weight loss programs on health enhancement among overweight women aged 40–60 years. Methods: This was a retrospective observational study that analyzed data from 145 overweight women in weight loss programs. Each woman joined one of four programs: 8 weeks of exercise plus diet (exe + nutr), 8 weeks of diet only (nutrition), 8 weeks of exercise only, or a control group. Women completed a psychological questionnaire and also underwent anthropometric tests, blood pressure checks, a predicted maximal oxygen consumption (VO2 max) test on an ergometer bicycle, a one-leg balance test, straight leg test, and a sit and reach test, both before and after the program. Participants also provided a blood sample. Results: All of the measured variables improved in the exe + nutr and nutrition programs when compared with the control group; the exe + nutr group improved the most: body mass index, −1.3 kg/m 2 ; body fat, −2.9%; lean body mass, +1.1; VO2 max, +4.8; body image, +1.02; and p  < 0.01. Conclusion: The hypothesis-generating findings showed that weight loss programs improved anthropometric, biochemical, physiological, physical, and psychological variables in women aged 40–60 years. The program that included diet restriction with exercise, guidance, and regular counseling showed the best results.